Functional Core/Shell Drug Nanoparticles for Highly Effective Synergistic Cancer Therapy. Issue 9 (25th March 2014) - Li, Wei; Zhang, Xiujuan; Zhou, Mengjiao; Tian, Baishun; Yu, Caitong; Jie, Jiansheng; Hao, Xiaojun; Zhang, Xiaohong
<x xml:space="preserve">Abstract</x> Gold (Au)‐nanoshelled 10‐hydroxycamptothecin nanoparticles (HCPT NPs) are developed with combination of photothermal therapy and chemotherapy for highly effective cancer therapy. The strong near‐infrared (NIR) absorbance from Au nanoshells endows the nanocomposites photothermal effects and on‐demand drug release. Notably, the drug‐loading content reaches up to 63.7 wt%, which is much higher than that in the previously reported nanovehicles systems. Both in vitro and in vivo studies indicate that the combined local specific chemotherapy with external NIR photothermal therapy demonstrates a synergistic effect, which is significantly better than either of them alone. More importantly, due to the high drug‐loading content and efficient photothermal effects of the nanocomposites, 100% in vivo tumor elimination is achieved at a low laser irradiation power density of 1 W cm−2 without weight loss and tumor recurrence. No obvious systematic toxicity is observed for the injected mice, indicating the good biocompatibility of this kind of multifunctional drug nanocomposites. This work highlights the great potential of drug–nanostructure‐based multifunctional core/shell nanpocomposite for highly efficient cancer therapy.